1994
DOI: 10.1002/cncr.2820741308
|View full text |Cite
|
Sign up to set email alerts
|

The abnormal mammogram radiographic findings, diagnostic options, pathology, and stage of cancer diagnosis

Abstract: An abnormal mammogram often will detect a mass, a cluster of calcifications, or both; these findings are not pathognomonic and require a tissue diagnosis to confirm the presence of invasive cancer, in situ cancer, or a nonmalignant process. Although mammography is very sensitive, its abnormalities may be nonspecific. Ultrasound may help to distinguish a cystic mass from a solid mass. The mammographic report should be concise and not vague and must provide the referring physician with clear information as to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Current limitations of mammography include the inability to evaluate radiographically dense breasts, which are common in Asian or younger women, and postoperative breasts, where scar is difficult to distinguish from recurrent tumours [2]. A systematic review also showed that a delay of 3 -6 months in symptomatic patients was associated with lower survival [3].…”
Section: Introductionmentioning
confidence: 98%
“…Current limitations of mammography include the inability to evaluate radiographically dense breasts, which are common in Asian or younger women, and postoperative breasts, where scar is difficult to distinguish from recurrent tumours [2]. A systematic review also showed that a delay of 3 -6 months in symptomatic patients was associated with lower survival [3].…”
Section: Introductionmentioning
confidence: 98%
“…This study observed a reasonably high sensitivity (87.5 %) of digital mammography for breast cancer in symptomatic patients under the age of 40 years, and our results mirror this finding. The primary abnormal mammographic findings in this study group were those of the classically described malignant mammographic findings [18]. The patients in this study that had ''normal or benign'' mammographic appearances (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Where zi is a random variable indicating intensity, p(zi) is the histogram of the intensity levels in a region, L is the number of possible intensity levels and (2) is the mean(average) intensity given by equation (2). Mean is the measure of average intensity.…”
Section: Statistical Approachesmentioning
confidence: 99%
“…[1] Many computer aided detection techniques are being implemented for the segmentation of these mammogram images and obtaining the desired region of interest, which are having high probability of occurrences masses. [2] In the digital mammogram images, various segmentation techniques are implemented for segmenting the lesions. Radial gradient index based algorithm and a probabilistic algorithm are two such techniques.…”
Section: Introdcutionmentioning
confidence: 99%